2006
DOI: 10.1007/s10834-006-9022-y
|View full text |Cite
|
Sign up to set email alerts
|

Retirement and Productive Activity in Later Life

Abstract: Aging, Productive activity, Retirement, Time use,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
39
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 14 publications
4
39
0
Order By: Relevance
“…The increased time spent in chores across retirement found in this longitudinal study is consistent with the findings of cross-sectional studies that compare retired people to those still working [7,8,12]. It may be that the demands of work put time pressure on carrying out chores, while retirement allows chores to be carried out at a more leisurely pace.…”
Section: Main Findingssupporting
confidence: 85%
See 1 more Smart Citation
“…The increased time spent in chores across retirement found in this longitudinal study is consistent with the findings of cross-sectional studies that compare retired people to those still working [7,8,12]. It may be that the demands of work put time pressure on carrying out chores, while retirement allows chores to be carried out at a more leisurely pace.…”
Section: Main Findingssupporting
confidence: 85%
“…For example, although men spend less time doing household chores than women at all life stages, they increase the time spent in chores around retirement, compared with women [7,8]. Similarly, previous studies have found an overall increase in recreational physical activity at retirement, but a decrease when considering only retirees from lower socioeconomic backgrounds [9,10].…”
Section: Introductionmentioning
confidence: 90%
“…Many couples plan their retirement together; people are less likely to continue working if their partner has already retired and vice versa [119]. Being happily married has a strong positive influence on retirement, as couples look forward to spending more time together [120,121]. However, couples individually and jointly reported to be most satisfied after retirement are those in which the female partner was not influenced by their male partner to retire [122].…”
mentioning
confidence: 99%
“…Some empirical research has attempted to examine individual differences in participation in productive activities among the elderly. For example, Dosman et al (2006) looked at differences in how people allocate time among productive and other activities pre-and postretirement. In this research, four broad categories were examined: self-care, leisure activities, paid work, and unpaid productive work.…”
Section: Introductionmentioning
confidence: 99%
“…Our definition of productive activity introduces unpaid work done for one's own household or for another individual's household, caring for family members or relatives, and unpaid work done in the community or for any other person or group (Dosman et al 2006).…”
mentioning
confidence: 99%